Fermentation for the production of biobased chemicals in a circular economy: a perspective for the period 2022–2050. Issue 17 (18th August 2022) - Ewing, Tom A.; Nouse, Niels; van Lint, Matthijs; van Haveren, Jacco; Hugenholtz, Jeroen; van Es, Daan S.
Abstract : A critical review of the potential of fermentation processes for production of bulk chemicals in a future circular economy. Abstract : Chemicals and materials produced from non-renewable, petrochemical feedstocks contribute greatly to the quality of life we currently enjoy. To ensure that quality of life is maintained in the future, it is imperative that we move towards a circular economy, where care is taken to reuse or recycle materials at their end-of-life and new chemicals and materials are sourced from renewable carbon feedstocks such as biomass. To achieve this transition, efficient conversion methods by which biomass-derived feedstocks can be converted to chemicals are required. The high degree of functionalisation ( i.e. high content of oxygen atoms) of biomass-derived feedstocks, makes their conversion by microbial fermentation an interesting option. This article provides an overview of currently available fermentation technologies that have the potential to play a role in the production of biobased bulk chemicals in a circular economy in the period up to 2050. Our focus is primarily on technologies that are sufficiently mature to have been implemented on (at least) industrial pilot scale. In addition to an overview of available technologies, we provide a critical assessment of their potential relevance for use in the production of bulk chemicals in a future circular economy. We conclude that seven fermentation processes for the production of (potential) bulk chemicals have already reached a stage of technological maturity where they are ready to be applied in a circular economy. A number of other processes may reach this stage of maturity in the coming years.